Neuroactive Steroids and Cognitive Functions in First-Episode Psychosis Patients and Their Healthy Siblings - Knytl, Pavel; Voráčková, Veronika; Dorazilová, Aneta; Rodriguez, Mabel; Cvrčková, Aneta; Kofroňová, Edita; Kuchař, Martin; Kratochvílová, Zuzana; Šustová, Petra; Čerešňáková, Silvie; Mohr, Pavel (Frontiers in Psychiatry, 2019)
Background: Neuroactive steroids (NAS) affect neurotransmitter systems and cognition; thus, they play role in etiopathogenesis of psychiatric disorders. Aims: The primary aim was to examine cognition and effects of NAS on cognitive functioning in first-episode psychosis patients and in their healthy siblings. The secondary aims were to verify whether cognitive deficit is an endophenotype of psychosis and whether higher NAS levels represent a high-risk factor for psychosis. Methods: Studied participants were 1) patients with first episode of psychosis, 2) healthy siblings of the patients, and 3) matching healthy controls. Study procedures included administration of a battery of neuropsychological tests assessing six cognitive domains and examination of NAS plasma levels [cortisol (CORT), 11-deoxycorticosterone (DOC), testosterone (TEST), dehydroepiandrostendione (DHEA), dihydrotestosterone (DHT), and progesterone (PROG)]. Results: A total of 67 subjects were analyzed (16 patients, 22 siblings, and 29 controls). Significant group differences were found in most of the cognitive domains; the patients had the lowest scores. The Kruskal–Wallis test revealed significant group differences in CORT levels (p < 0.01), TEST (p < 0.01), and DHT (p < 0.001); no difference was found in PROG, DHEA, and DOC. All cognitive domains, except for attention, were affected by the NAS levels. CORT levels of patients correlated with speed of processing (r = 0.55) and working memory (r = 0.52), while PROG levels correlated with abstraction (r = −0.63). In siblings, there was a negative correlation between TEST levels and verbal memory (r = −0.51) and PROG with attention (r = −0.47). Conclusions: Our results verified that individual domains of cognitive deficit (abstraction and verbal memory) can be considered as an endophenotype of psychosis. Higher levels of cortisol and testosterone in siblings are consistent with high-risk states for psychosis. Multiple interactions between NAS and cognitive functioning, particularly memory functions, were observed. Study limitations (small sample size and administration of antipsychotic medication) did not allow us to establish unequivocally NAS as an endophenotype.